Geographic distribution of the 20210 G to A prothrombin variant - Rosendaal, F R; Doggen, C J; Zivelin, A; Arruda, V R; Aiach, M; Siscovick, D S; Hillarp, A; Watzke, H H; Bernardi, F; Cumming, A M; Preston, F E; Reitsma, P H (Thrombosis and haemostasis, 1998)
A variant in prothrombin (clotting factor II), a G to A transition at nucleotide position 20210, has recently been shown to be associated with the prothrombin plasma levels and the risk of both venous and arterial thrombosis. The purpose of this study was to investigate the prevalence of carriership of this mutation in various populations. We combined data from 11 centres in nine countries, where tests for this mutation had been performed in groups representing the general population. We calculated an overall prevalence estimate, by a precision-weighted method, and, since the distribution of the prevalences did not appear homogeneous, by an unweighted average of the prevalences. We examined differences in the prevalences by geographical location and ethnic background as a possible explanation for the heterogeneity. Among a total of 5527 individuals who had been tested, 111 heterozygous carriers of the 20210A mutation were found. The prevalence estimates varied from 0.7 to 4.0 between the centres. The overall prevalence estimate was 2.0 percent (CI95 1.4-2.6%). The variation around the summary estimate appeared more than was expected by chance alone, and this heterogeneity could be explained by geographic differences. In southern Europe, the prevalence was 3.0 percent (CI95 2.3 to 3.7%), nearly twice as high as the prevalence in northern Europe (1.7%, CI95 1.3 to 2.2%). The prothrombin variant appeared very rare in individuals from Asian and African descent. The 20210A prothrombin variant is a common abnormality, with a prevalence of carriership between one and four percent. It is more common in southern than in northern Europe. Since this distribution within Europe is very different to that of another prothrombotic mutation (factor V Leiden or factor V R506Q), founder effects are the most likely explanation for the geographical distribution of both mutations.